UV-trained and metal-enhanced fluorescence of biliverdin and biliverdin nanoparticles. Issue 9 (12th January 2021) - Fathi, Parinaz; Roslend, Ayman; Mehta, Kritika; Moitra, Parikshit; Zhang, Kai; Pan, Dipanjan
Abstract : UV irradiation and metal chelation can be utilized alone or in combination to tailor the fluorescence behavior of biliverdin-based imaging probes at selected wavelengths. Abstract : Increasing the fluorescence quantum yield of fluorophores is of great interest for in vitro and in vivo biomedical imaging applications. At the same time, photobleaching and photodegradation resulting from continuous exposure to light are major considerations in the translation of fluorophores from research applications to industrial or healthcare applications. A number of tetrapyrrolic compounds, such as heme and its derivatives, are known to provide fluorescence contrast. In this work, we found that biliverdin (BV), a naturally-occurring tetrapyrrolic fluorophore, exhibits an increase in fluorescence quantum yield, without exhibiting photobleaching or degradation, in response to continuous ultraviolet (UV) irradiation. We attribute this increased fluorescence quantum yield to photoisomerization and conformational changes in BV in response to UV irradiation. This enhanced fluorescence can be further altered by chelating BV with metals. UV irradiation of BV led to an approximately 10-fold increase in its 365 nm fluorescence quantum yield, and the most favorable combination of UV irradiation and metal chelation led to an approximately 18.5-fold increase in its 365 nm fluorescence quantum yield. We also evaluated these stimuli-responsive behaviors in biliverdin nanoparticles (BVNPs) at the bulk-state and single-particle level. We determined that UV irradiation led to an approximately 2.4-fold increase in BVNP 365 nm quantum yield, and the combination of UV irradiation and metal chelation led to up to a 6.75-fold increase in BVNP 365 nm quantum yield. Altogether, these findings suggest that UV irradiation and metal chelation can be utilized alone or in combination to tailor the fluorescence behavior of imaging probes such as BV and BVNPs at selected wavelengths.